The elements of C++ style - Misfeldt, Trevor (Cambridge University Press, 2004)
The book provides conventions for formatting, naming, documentation, programming, and packaging for the latest ANSI standard of C++, and also includes discussion of advanced topics such as templates. Trevor Misfeldt is co-author of Elements of Java Style (Cambridge, 2000) and CEO of CenterSpace Software. Gregory Bumgardner is a Freelance Consultant with twenty-five years of experience in software design and implementation. He is co-author of Elements of Java Style (Cambridge, 2000). Andrew Gray is Director of Engineering for Intellichem, Inc. He was previously Software Engineering Manager and Technology Evangelist at Rogue Wave Software, where he led the development of XML infrastructure solutions